Knotted ureteral single‐J stent in a patient with ureterocutaneostomy. Issue 6 (5th August 2021) - Koike, Yuhei; Urabe, Fumihiko; Iwatani, Kosuke; Nukariya, Yuto; Tanaka, Masatoshi; Tashiro, Kojiro; Kimura, Takahiro; Tsuzuki, Shunsuke; Egawa, Shin
Abstract : Introduction: Although ureteral stent catheterization is a common procedure in urological practice, knotting of a ureteral catheter is a very rare complication. Case presentation: A 62‐year‐old man underwent cystectomy and ureterocutaneostomy for bladder cancer. The ureteral single‐J stent was changed every month postoperatively without complications. However, at postoperative 30 months, resistance was experienced while adjusting the stent position after the exchange. Abdominal radiography revealed knotting of the stent at the right renal pelvis. The knotted stent was percutaneously removed because the patient had only one functioning kidney. A nephrostomy tract was established and the ureteral stent was exchanged. No complications occurred in the perioperative period. Conclusion: We encountered a case of a knotted ureteral single‐J stent in a man treated with ureterocutaneostomy. In this case, resistance was noticed during extraction; the possibility of stent knotting should always be considered, and an appropriate removal strategy must be planned.